Vitamin D Supplementation in women with Diminished Ovarian Reserve: A Randomized Controlled Trial - Halder, Suravi; Ishrat, Shakeela; Rahman, Farzana; Nasrin, Ivy; Amir, Mumtahena; Majumdar, Bipul Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Diminished ovarian reserve (DOR) predicts decreased ovarian response to stimulation. Low serum anti-Mullerian hormone (AMH) is associated with DOR. AMH is a marker of ovarian reserve and acts as a predictor of ovarian response to ovarian stimulation protocol. The AMH is up regulated by vitamin D via vitamin D response elements that bind the vitamin D receptor. Vitamin D supplementation has a role in increasing serum AMH. The objective was to compare the combined effect of vitamin D and DHEA vs DHEA alone on serum AMH in DOR. Methods: This randomized controlled trial was conducted in the Department of Reproductive Endocrinology and Infertility, Bangabandhu Sheikh Mujib medical University (BSMMU), Dhaka, from March 2021 to February 2022. A total of 44 infertile women with DOR, 20 to 39 years were allocated into two groups, one received vitamin D plus DHEA for 8 weeks and the other received DHEA alone for the same duration. After 8 weeks of treatment, both groups had repeat assessment of AMH, FSH and transvaginal sonography for AFC. Results: There was no significant difference in serum AMH after vitamin D supplementation in women with DOR. But the spontaneous pregnancy during intervention was 2.57 times more in those given vitamin D supplementations in addition to dehydroepiandrosterone (DHEA). Conclusions: Short term vitamin D supplementation adds little to the effect of increasing AMH but favors spontaneous pregnancy in women with DOR.